Concrete like a nation is ambitious - Simon, S. (2016)
The design and construction of the Faculty of Economics and Administration building at the University of Malaya in the late 1960s was an occasion to reflect on the political and economic imperatives that underlie the will-to-form of Malaysia, as a newly constituted nation state in 1963. The structure is designed by Goh Hock Guan, who was the first (or debatably second) Secretary General of the Democratic Action Party (an offshoot of Lee Kwan Yew's People's Action Party Singapore following the separation of Singapore from Malaysia in 1965). That an opposition party leader was able to design an important building project suggests that there was a moment where bi-partisan cooperation was still possible, even if that moment seldom recognised in today's divisive political climate. With a lecture hall that is shaped like a blooming lotus, the architect was hoping to express the economic and administrative ideals of the 1960s. The building in a sense, also inadvertently captured some of the paradoxes of a desire for a centralised economy that was aimed at eradicating poverty. This was known in its days as the Great Economics Debate. Research in postwar art history has often favoured a narrative of political resistance or a vaguely worded concept of nation-building. It seldom attends to the economic undercurrent that was also palpably shaping the plastic ambition behind the use of concrete in brutalist architecture. This presentation provokes questions about the intersection between concrete form and centralised economy, a desire for internationalism and the creation of a class of future technocrats, as well as the changing conception of the university and its post-colonial foibles.